Human Respiratory Syncytial Virus-Induced Immune Signature of Infection Revealed by Transcriptome Analysis of Clinical Pediatric Nasopharyngeal Swab Samples. (29th July 2020) - Nicolas De Lamballerie, Claire; Pizzorno, Andrés; Dubois, Julia; Padey, Blandine; Julien, Thomas; Traversier, Aurélien; Carbonneau, Julie; Orcel, Elody; Lina, Bruno; Hamelin, Marie-Eve; Roche, Magali; Textoris, Julien; et al.
Abstract: Human respiratory syncytial virus (HRSV) constitutes one the main causes of respiratory infection in neonates and infants worldwide. Transcriptome analysis of clinical samples using high-throughput technologies remains an important tool to better understand virus-host complex interactions in the real-life setting but also to identify new diagnosis/prognosis markers or therapeutics targets. A major challenge when exploiting clinical samples such as nasal swabs, washes, or bronchoalveolar lavages is the poor quantity and integrity of nucleic acids. In this study, we applied a tailored transcriptomics workflow to exploit nasal wash samples from children who tested positive for HRSV. Our analysis revealed a characteristic immune signature as a direct reflection of HRSV pathogenesis and highlighted putative biomarkers of interest such as IP-10, TMEM190, MCEMP1, and TIMM23. Abstract : This study applied a tailored transcriptomics workflow to exploit nasal wash samples from HRSV-positive hospitalized children. The transcriptional immune signature appears as a direct reflection of HRSV pathogenesis and highlights putative biomarkers of interest.